Tracing the Oldest Audio Recordings of Vocal Musical Tradition of Germans in Bačka. The Field Research of Gustav Kipers-Sonenberg in Bačka - Vesna Ivkov (University of Belgrade, 2016)
This paper represents an attempt by the author to contribute to the history of ethnomusicology in Serbia, by brining to light new data on the fieldwork conducted by Gustav Kipers – Sonenberg in Bačka for the purposes of making audio recordings and collecting German traditional melodies. The aim of the research is to study the opinions of contemporary members of the German national community in Bačka on the melodies gathered by Gustav Kipers – Sonenberg. This approach and the data gathered become the basis for considering further directives for the study of German traditional music in Serbia.